Development and Physicochemical Characterization of a Poly-Herbal Hydrosol-Based Intranasal Spray for the Management of Rhinosinusitis: Research Article (Journal of Pharma Insights and Research, 2026)
Rhinosinusitis is characterized by the inflammation of the paranasal sinus mucosa, often resulting from microbial infections, environmental allergens, or structural obstructions. While conventional pharmacotherapy involving synthetic decongestants and corticosteroids provides symptomatic relief, prolonged administration frequently leads to adverse effects such as rhinitis medicamentosa, mucosal atrophy, and systemic absorption. A natural therapeutic alternative was developed by utilizing the synergistic properties of medicinal plant hydrosols. A poly-herbal nasal spray was formulated incorporating aromatic distillates of Eucalyptus globulus, Matricaria chamomilla, Zingiber officinale, Ocimum sanctum, and Mentha piperita. These plant sources were selected for their established antimicrobial, anti-inflammatory, mucolytic, and decongestant activities. The formulation was stabilized using sodium chloride for isotonicity, glycerin as a humectant, and sodium benzoate as a preservative, with the final pH adjusted to maintain compatibility with the nasal microenvironment. Evaluation of the physicochemical parameters revealed a pH of 6.0, optimal viscosity for mucosal retention, and a uniform spray pattern ensuring effective drug distribution. In-vitro diffusion and sterility testing confirmed the controlled release profile and safety of the preparation. The absence of irritation in safety models suggests that the multi-hydrosol spray is a biocompatible alternative to synthetic formulations. This natural method addresses the effects of sinusitis by simultaneously reducing inflammation, facilitating mucus clearance, and inhibiting pathogenic growth. The results from this study show the potential for utilizing herbal distillates as a primary or adjunctive treatment in upper respiratory inflammatory conditions